Statistical Predictions of Electric Load Profiles in the UK Domestic Buildings - Ihbal, A. M.; Rajamani, H. S.; Abd-Alhameed, R.A.; Jalboub, M. K. (Iraqi Journal for Electrical and Electronic Engineering, 2011)
This paper presents a method of generating realistic electricity load profile data for the UK domestic buildings. The domestic space features have been investigated excluding the heating and hot water systems. A questionnaire survey was conducted and the feedback were collected from a number of occupants at different intervals of times on daily bases in order to establish the probabilistic record of the estimated use of electrical appliances. The model concept of this study also considers the results of previous investigations such as that available in public reports and statistics as input data elements to predict the global domestic energy consumption. In addition, the daily load profile from individual dwelling to community can be predicted using this method. The result of the present method was compared to available published data and has shown reasonable agreement.